Biallelic loss‐of‐function variants in RBL2 in siblings with a neurodevelopmental disorder. Issue 3 (27th February 2020) - Brunet, Theresa; Radivojkov‐Blagojevic, Milena; Lichtner, Peter; Kraus, Verena; Meitinger, Thomas; Wagner, Matias
Abstract: The RBL2 locus has been associated with intelligence and educational attainment but not with a monogenic disorder to date. RBL2 encodes p130, a member of the retinoblastoma protein family, which is involved in mediating neuron survival and death. Previous studies on p130 knockout mice revealing embryonic death and impaired neurogenesis underscore the importance of RBL2 in brain development. Exome sequencing in two siblings with severe intellectual disability, stereotypies and dysmorphic features identified biallelic loss‐of‐function variants c.556C>T, p.(Arg186Ter) and a deletion of exon 13–17 in RBL2 (NM_005611.3), establishing RBL2 as a candidate gene for an autosomal recessive neurodevelopmental disorder.